Will Liberalizing the Services Trade between Developing and Developed Countries Solve Employment Problems in a Post-Pandemic Recovery? The Case of ACP-EU Services Trade - Manitra A. Rakotoarisoa (SocioEconomic Challenges)
The COVID-19 pandemic has exacerbated the asymmetric employment problems in the global services sector. Would a liberalization of the highly protected services trade between the rich and poorer countries help solve such problems? This paper contributes to answering that question by analyzing the impacts on welfare and employment of an hypothetical liberalization of the services trade between the Africa, Caribbean and Pacific Group of States (ACP) and their rich partners in the European Union and the United Kingdom (EU+UK). For both the ACP and EU +UK, their service sectors play important role in their economy, especially in providing jobs. The services sectors employ the majority of unskilled labor and the large majority of skilled labor. For instance, in the EU+UK, 67% of employed unskilled and 82% of employed skilled workers are in the service sectors; the respective figures for ACP countries are 54% and 90%. These figures indicate that any change in trade policies for the services sector will affect not just the services but also other sectors such agriculture and manufacturing in ACP and EU countries. To analyze the impacts of services trade liberalization on welfare an employment, I use a Computable General Equilibrium model that takes into account the labor productivity gaps among trading countries. Results show that although ACP services represents only about 24% of ACP’s total exports to and 28% of ACP’s total import from the EU+UK, halving the bilateral tariffs in services trade will generate for the ACP a welfare gain 3.4 times larger than the gain under elimination of bilateral tariffs on goods. Such liberalization of services trade will generate significant endowment effects equivalent to 410,000 new jobs per year, mostly in the services sector. The employment and welfare gains will also reach other sectors, including agriculture, as services trade costs are reduced. The liberalization of services trade will raise wages, especially for ACP’s skilled labor. All these ACP’s gains will increase further if its labor productivity improves. Despite a slight decline in wages for EU+UK’s skilled labor, the EU+UK will gain about 7.8 billion USD in welfare. Overall, liberalization of the services trade between ACP and EU+UK will help solve their employment problems and should not be delayed.